2018
DOI: 10.1021/acs.jafc.8b02732
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Butyrate Mitigates iE-DAP Induced Inflammation Caused by High-Concentrate Feeding in Liver of Dairy Goats

Abstract: The aim of this study is to explore the impact of sodium butyrate on d-glutamyl- meso-diaminopimelic acid (iE-DAP)-induced liver inflammation in dairy goats during subacute ruminal acidosis (SARA) caused by high-concentrate feed. To achieve this aim, 12 lactating dairy goats were randomly divided into two groups: a high-concentrate feed group ( n = 6, concentrate/forage = 6:4) as the control group and a sodium butyrate (SB) with high-concentrate feed group ( n = 6, concentrate/forage = 6:4, with 1% SB by wt.) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 60 publications
(187 reference statements)
1
16
0
Order By: Relevance
“…There are several reasons. Firstly, sodium butyrate improved the rumen pH and comprehensively decreased the bacterial cell wall components (LPS, PGN and LTA) in rumen fluid and plasma, which was consistent with previous studies [ 10 , 14 , 15 ]. Sodium β -hydroxybutyrate also improved rumen pH, but to a less extent than sodium butyrate.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…There are several reasons. Firstly, sodium butyrate improved the rumen pH and comprehensively decreased the bacterial cell wall components (LPS, PGN and LTA) in rumen fluid and plasma, which was consistent with previous studies [ 10 , 14 , 15 ]. Sodium β -hydroxybutyrate also improved rumen pH, but to a less extent than sodium butyrate.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, several studies have suggested that supplementation of sodium butyrate could comprehensively reduce the body injuries induced by HC diet in ruminants. These injuries included inflammation in the mammary gland [ 12 , 14 ], liver [ 15 ], rumen epithelium [ 17 ]; apoptosis in mammary cells [ 54 ] and hepatocytes [ 13 ]; and impairment of ruminal epithelium barrier function [ 10 ]. β -Hydroxybutyrate also possesses an anti-inflammatory activity via activating GPR109A [ 30 ] and decreasing the expression of innate immune genes [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells were harvested for total RNA extraction, and cDNA was obtained by RT-PCR. Relative quantification of candidate gene expressions was conducted using previously published primers of endogenous reference genes and target genes ( 30 34 ) ( Supplementary Table 2 ). The relative mRNA expression levels of candidate genes were calculated by the 2- ΔΔCt method.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were harvested for total RNA extraction and cDNA obtained by reverse-transcription PCR. Relative quantification of candidate gene expression was conducted using previously published primers [ 29 33 ] of endogenous reference and candidate genes (Additional file 2 : Table S2). Based on the 2 −ΔΔCq method, the relative levels of target gene transcription were normalized to reference gene expression.…”
Section: Methodsmentioning
confidence: 99%